Capoeira Angola Diversifying the University: : sowing an Ecology of Knowledges in the Performing Arts - Gallep, Cristiano de Mello (Revista Brasileira de Estudos da Presença, 2022)
Using testimonies from students after one semester practicing the art of capoeira, we underscore the potentiality of Capoeira Angola for actor training, as well as for promoting the self-knowledge of human beings and their social action. It is the playfulness and complexity of Capoeira Angola’s martial game, congregating space-body skills, music and poetry, in addition to a history of resistance and resilience as African heritage, constructing an Ecology of Knowledges that contributes to performing arts training and also to the embracing of Afro-diasporic popular culture by Brazilian universities.